2023
DOI: 10.1039/d2dd00096b
|View full text |Cite
|
Sign up to set email alerts
|

Unified graph neural network force-field for the periodic table: solid state applications

Abstract: Classical force fields (FF) based on machine learning (ML) methods show great potential for large scale simulations of solids. MLFFs have hitherto largely been designed and fitted for specific systems...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 73 publications
0
29
0
Order By: Relevance
“…However, other studies have found that the difference in scale between inter- and intramolecular interactions means that capturing both with a single model is often limiting and that training separate intermolecular and intramolecular models yields improved performance. , Partitioning the energy will also make applying the workflow over multiple landscapes more practical, which could allow for training transferable rather than system-specific models. The development of universal models for organic molecules , and inorganic materials, has produced impressive results with good transferability; similar models for organic crystals could have an important impact in the field of CSP.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have found that the difference in scale between inter- and intramolecular interactions means that capturing both with a single model is often limiting and that training separate intermolecular and intramolecular models yields improved performance. , Partitioning the energy will also make applying the workflow over multiple landscapes more practical, which could allow for training transferable rather than system-specific models. The development of universal models for organic molecules , and inorganic materials, has produced impressive results with good transferability; similar models for organic crystals could have an important impact in the field of CSP.…”
Section: Discussionmentioning
confidence: 99%
“…Models generated in this way are typically expected to be directly applicable to downstream tasks in which the explored configurations are effectively covered by the training data. Some examples include models such as M3GNet [15], CHGNet [16] and MACE-MP-0 [17], which are all trained on snapshots from DFT relaxations of the Material Project [18] structures, with M3GNet utilizing 88k configurations across 89 chemical species and both CHGNet and MACE-MP-0 being trained on 1.58M inorganic crystal frames from the concurrently introduced MPtraj dataset [16]; GNoME [19], trained on a dataset of inorganic crystals also starting from MP, but nearly two orders of magnitude larger than MPtrj; PreFerred Potential (PFP), trained on approximately 9M frames of 45 elements [20]; and ALIGNN, trained on 307K data frames of 89 elements [21]. However, several limitations exist: (1) Simultaneously training multiple datasets from different application fields is not feasible due to the variations in labeling with different DFT settings.…”
Section: Mainmentioning
confidence: 99%
“…Machine learning potentials (MLPs) have recently emerged as highly promising tools in computational materials science due to their near-DFT accuracy, nearly linear scaling with system size, and exceptional transferability to diverse chemical environments. Prominent examples of MLPs include neural network potentials (NNPs), Gaussian approximation potentials, , moment tensor potentials, spectral neighbor analysis potentials, atomic CE potentials, , and graph NNPs. The high flexibility of MLPs allows for broad applicability across different types of matter, encompassing bulk and 2D crystals, amorphous materials, , liquids, interfaces, , and clusters. , In the domain of disordered systems, MLPs were employed to investigate binary alloys spanning a wide range of compositions, high-entropy alloys, and grain boundaries. However, a conspicuous gap exists in the literature concerning the application of MLPs to nonstoichiometric systems characterized by varying elevated vacancy concentrations. Herein, we address this gap by examining the efficacy of NNPs for modeling nonstoichiometric chromium sulfides, a material that has not been explored in the existing literature using either machine learning or conventional potentials.…”
Section: Introductionmentioning
confidence: 99%